System Information Sales At The Bayeprive Boutique In Serang City Are Web-Based Using The Laravel Framework - Iim Rohaimudin; Sigit Auliana; Gagah Dwiki Putra Aryono (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
The development of information technology offers significant opportunities to support business efficiency, including in the retail sector, such as clothing boutiques. The Baye Prive boutique in Serang City still uses a manual system for its sales operations, which causes various obstacles such as recording errors and limited market reach. This study aims to design a web-based sales information system to simplify the transaction process, stock management, and real-time reporting. The Laravel framework was chosen because of its ability to build structured applications with a Model-View-Controller (MVC) approach. The system development method used is the Waterfall model, starting from the requirements analysis stage to the maintenance stage. The developed system provides key features such as a product catalog, shopping cart, payment, and reporting dashboard. This system is accessible to both admins and customers, supporting the digitalization of the sales process and expanding marketing reach beyond the region. The implementation of this system is expected to improve efficiency, accuracy, and customer service. The results show that the designed system successfully overcomes the weaknesses of the manual system and provides an effective digital solution for the boutique's needs.